IMPLEMENTASI SISTEM INFORMASI PENJUALAN BERBASIS CLIENT-SERVER (Studi Kasus: PT. SAMAFITRO CABANG BANDUNG) - Rio Yunanto; Agus Muchtar; Dony Waluya Firdaus (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2012)
Samafitro's Branch Office is located in Bandung at 229th RE. Martadinata street. The problems before implementation of Sales Information System, sales activities was records and calculations by paper based. They are could result in human error, so that the accounting process and the generating reports are less quickly and accurately. Type of research that is using academic research. type of data that is using quantitative data and qualitative data. Research methods that is using explanatory and descriptive research. Technique of data collection that is using field research that consists of interview, observation and library research. Structure of system development that is using Waterfall. Financial reporting in Sales Information System of Samafitro in accordance with financial accounting standards. The computerized data processing is well, there by reducing the occurrence of human error and produce sales reports in the Supevisor Sales and supporters report on the accounts receivable in Supervisor Accounting.